Strategi Kepemimpinan Partisipatif Kepala Sekolah dalam Meningkatkan Kolaborasi di Sekolah MA Ma’arif Balong - Hidayatulloh, Aswin; KR, M Indi; subkhana, taqi; fathoni, tamrin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Indonesia is the 6th most indebted country, 3rd most corrupt country, 112th out of 127 countries in human resources ranking with 30% of the population living below the poverty line and 12 million open unemployed. Improving collaboration in schools is an important step in creating a more effective and enjoyable learning environment. Collaboration not only involves interactions between teachers and students but also involves parents, communities and various other stakeholders. The participatory leadership model is often defined as a principal who involves active participation from various parties, such as teachers, students, parents, the community, and all those related to the teaching and learning process in the educational institution. in the study entitled ‘Principal's Participatory Leadership Strategy in Improving Collaboration in Schools’ is through literature review. Literature review is a research method that includes searching, collecting, and analysing information contained in written works or sources such as books, journal articles, theses, and other related documents. By applying participatory leadership, the Principal of MA Ma'arif Balong can create a school environment that is inclusive, innovative, and focused on student needs.